Older adult-onset Alexander disease with atypical clinicoradiological features: a case report - Kang, You-Ri; Nam, Tai-Seung; Kim, Jae-Myung; Kang, Kyung Wook; Lee, Seung-Han; Choi, Seong-Min; Kim, Myeong-Kyu (Frontiers in Neurology, 2023)
Alexander disease (AxD) is a rare autosomal dominant astrogliopathy caused by mutations in the gene encoding for the glial fibrillary acidic protein. AxD is divided into 2 clinical subtypes: type I and type II AxD. Type II AxD usually manifests bulbospinal symptoms and occurs in the second decade of life or later, and its radiologic features include a tadpole-like appearance of the brainstem, ventricular garlands, and pial signal changes along the brainstem. Recently, eye-spot sign in the anterior medulla oblongata (MO) has been reported in patients with elderly-onset AxD. An 82-year-old woman presented with mild gait disturbance and urinary incontinence without bulbar symptoms. The patient died 3 years after symptom onset because of rapid neurological deterioration after a minor head injury. MRI showed the signal abnormalities resembling angel-wings in the middle portion of the MO along with hydromyelia of the cervicomedullary junction. Herein, we report the case of this patient with older adult-onset AxD with an atypical clinical course and distinct MRI findings.